Institutional Cross-Ownership and Corporate Social Responsibility: Does Product Market Competition Matter? - Nizar, Hamza; Hamza, Taher (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2024)
This paper investigates the relationship between institutional cross-ownership and corporate social responsibility and whether product market competition moderates this relationship. Based on a sample of French firms over 2001–2015, we found that institutional cross‑ownership positively affects corporate social responsibility. Our finding suggests that the monitoring experience gained by institutional cross-owners leads them to increase corporate social responsibility by fostering industry coordination between cross-owned firms. This positive effect is less likely in highly competitive product markets which advocates that competitive pressure may make industry coordination more difficult. Cross-owned firms may then prioritize maintaining a profitable margin over pursuing corporate social responsibility activities.